2001
DOI: 10.1007/s10240-001-8190-4
|View full text |Cite
|
Sign up to set email alerts
|

Deux caractérisations de la mesure d'équilibre d'un endomorphisme de P k (C)

Abstract: par JEAN-YVES BRIEND et JULIEN DUVAL RÉSUMÉ. -Soit µ la mesure d'équilibre d'un endomorphisme de P k (C). Nous montrons ici qu'elle est son unique mesure d'entropie maximale. Nous construisons directement µ comme distribution asymptotique des préimages de tout point hors d'un ensemble exceptionnel algébrique.ABSTRACT. -Let µ be the equilibrium measure of an endomorphism of P k (C). We show that it is its unique measure of maximal entropy. We build µ directly as the distribution of premiages of any point outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
27

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 11 publications
(15 reference statements)
1
62
0
27
Order By: Relevance
“…Let us see how we deduce (6), thus completing the proof of Theorem 2.1. Since the sets of P n (x) are pairwise disjoint, we have:…”
Section: Proposition 57mentioning
confidence: 99%
See 1 more Smart Citation
“…Let us see how we deduce (6), thus completing the proof of Theorem 2.1. Since the sets of P n (x) are pairwise disjoint, we have:…”
Section: Proposition 57mentioning
confidence: 99%
“…Fornaess and Sibony [14] proved that μ is mixing and that log Jac f ∈ L 1 (μ). Briend and Duval [5] established that the exponents of μ are bounded below by log √ d and that μ is the unique measure of maximal entropy (h μ = log d k ) [6]. Concerning the Hausdorff dimension of μ, Mañé's formula asserts that dim H μ = log d/λ when k = 1.…”
Section: Application To the Equilibrium Measure μ Of Fmentioning
confidence: 99%
“…This exceptional set is still not well understood, its study seems to require new ideas. Very recently, Briend-Duval [2] showed that using a dynamical argument, as in our work [6,8,10], one can obtain a short proof of Corollary 1.4, see also [6,Prop. 2.4] for a more general setting.…”
Section: Introductionmentioning
confidence: 99%
“…Fornaess-Sibony proved that µ is mixing [22] and Briend-Duval that µ is the unique measure of maximal entropy [7].…”
mentioning
confidence: 99%